Pengaruh Budaya Organisasi Dan Kompleksitas Tugas Terhadap Peserta Magang Maupun Probation Di Kantor Akuntan Publik (KAP) Studi Kasus Mahasiswa Atau Alumni UNPAR - Katharina Audy Onwardhani (Jurnal Riset Akuntansi, 2023)
This study aims to examine the influence of organizational culture and complexity duties on the performance of apprentices and probation participants at the Public Accounting Firm (KAP). This research is still relevant as evidenced by the existence of cases of fraud and audit failures caused by the performance of auditors in public accounting firms that have not been optimum. The research technique used was a questionnaire with 76 auditors as respondents from Public Accounting Firms in Indonesia. The auditors come from active students or alumni of UNPAR accounting who are apprentices and alumni who have attended probation at KAP. The research method used in testing the hypothesis is validity and reliability testing, multiple linear regression, F test (simultaneous), and t test (partial) with the independent variables namely organizational culture and task complexity while the dependent variable is auditor performance at KAP. The results of data processing show that all independent variables in this study which include organizational culture and task complexity have a significant effect both partially and simultaneously on auditor performance. With this research, the researcher hopes that further researchers can expand this research by adding other variables that are factors that influence the performance of an auditor